Ease of Doing Business amidst COVID-19 Pandemic: A Case Study of Rajasthan. Issue 2 (June 2022) - Choudhary, Boola; Choudhary, Chitra; Bhatnagar, Sumedha
The present study attempts to highlight the overview of the regulatory reforms undertaken by Government of Rajasthan and also investigates the impact of COVID-19 on the small businesses of the state. The study is based upon primary survey. The result of the survey depicts that the regulatory reforms undertaken by the state have positive effect on the businesses, though the existing reforms could only provide limited support to the losses incurred by business during the time of pandemic. The results highlight that the key challenges faced by all the businesses include repayment and acquiring loans, payment of wages and salaries, weakening of demand and retaining of workforce. The effective ways to support the revival from losses include technological innovations, increase the sales and demand for goods, lowering of the cost to business along with the incentives and bailout packages given by the government. The study gives the perception of businesses that can help policymakers and public representatives to design state-specific strategic plan for the revival of businesses from the losses caused during the pandemic.